1969
DOI: 10.32473/edis-hr017-2002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Motivation: An Effective Tool for Managers

Abstract: This is EDIS document HR 017, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2002. https://edis.ifas.ufl.edu/hr017

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…They have no sense of growth and progress in their profession. Herzberg regards these two factors as two motivating ones [27]. The results of our study showed that the development of an atmosphere for mutual growth and excellence, as a job promotion facilitator, emphasize the two dimensions of individual and organizational promotion.…”
Section: Discussionmentioning
confidence: 52%
“…They have no sense of growth and progress in their profession. Herzberg regards these two factors as two motivating ones [27]. The results of our study showed that the development of an atmosphere for mutual growth and excellence, as a job promotion facilitator, emphasize the two dimensions of individual and organizational promotion.…”
Section: Discussionmentioning
confidence: 52%
“…According to Mumford (1991), Job satisfaction can be analyzed and rated in terms of the fit between what the company requires and what employees want, as well as the fit between what the person wants and what they actually get. Furthermore, numerous authors have pointed out that employee satisfaction is the outcome of a combination of benefits rather than a single reward (Bessell, Dicks, Wysocki, & Kepner, 2002).…”
Section: The Ocem Journal Ofmentioning
confidence: 99%
“…And, on the other hand, the company's management should conduct those actions directed at the staff's efforts to fully achieve the organization's goals. However, Bessell et al (2002) found that there should be thinking about incentives and recognition, it is also a good idea to recognize career growth and where people are in their careers. Pay rewards, for example, may appeal to young employees, opportunities for professional advancement may interest mid-career associates, and being part of policy and strategic planning may interest longterm associates.…”
Section: Table 3 Assessment On Motivation Factors Of Agripreneurs In Terms Of Job Characteristicsmentioning
confidence: 99%